Patient-reported outcomes in performance measurement - Cella, David (RTI Press Publication, 2015)
Patient-reported outcomes (PROs) are measures of how patients feel or what they are able to do in the context of their health status; PROs are reports, usually on questionnaires, about a patient's health conditions, health behaviors, or experiences with health care that individuals report directly, without modification of responses by clinicians or others; thus, they directly reflect the voice of the patient. PROs cover domains such as physical health, mental and emotional health, functioning, symptoms and symptom burden, and health behaviors. They are relevant for many activities: helping patients and their clinicians make informed decisions about health care, monitoring the progress of care, setting policies for coverage and reimbursement of health services, improving the quality of health care services, and tracking or reporting on the performance of health care delivery organizations. We address the major methodological issues related to choosing, administering, and using PROs for these purposes, particularly in clinical practice settings. We include a framework for best practices in selecting PROs, focusing on choosing appropriate methods and modes for administering PRO measures to accommodate patients with diverse linguistic, cultural, educational, and functional skills, understanding measures developed through both classic and modern test theory, and addressing complex issues relating to scoring and analyzing PRO data.